IMPLEMENTATION OF A WEB-BASED PENDING PRODUCT INFORMATION SYSTEM AT PT SUGINDO INTERNATIONAL - Hermawati, Karmila; Rivatunisa, Cyntia (INFOKOM (Informatika & Komputer), 2025)
In today’s digital era, the use of information technology is essential to improve work efficiency and effectiveness across various sectors, including the industrial sector. PT Sugindo International previously employed a manual method using paper- based forms to report problematic (abnormal) products that required decisions from the Quality Control (QC) department. This method was considered inefficient and prone to data loss and delays in information delivery. This study aims to design and implement a web-based information system that enables operators to input data on abnormal products to be placed in a pending area, and allows QC to provide decisions regarding those products. The system is designed to be accessible only to company employees through a login process based on their respective departments, thereby maintaining data security and confidentiality. The system was developed using a UML modeling approach, including use case and activity diagrams. The results show that the system significantly improves the speed, efficiency, and documentation of the reporting and handling process of pending products. Moreover, it enhances real-time coordination between the production and QC departments without relying on paperbased communication.